Comparison of Molecular Structures with DFT and HF of Isoxazoline and Isoxazolidine - Kara, Y.S.; Sagdinc, S.G. (Asian Journal of Chemistry, 2013)
Quantum chemical methods [density functional theory (DFT), ab initio (HF) and semi emperical methods] have given to be very important information about the molecular structure in addition to elucidating the electronic structure and reactivity. They have also proved to be a useful tool for studying inhibition mechanisms. In the present study, quantum chemical calculations using the density functional theory and ab initio (HF) methods have been performed on three isoxazoline and three isoxazolidine derivatives used as corrosion inhibitors to found the relationship between molecular structure and their inhibition efficiencies. The corresponding structures have been optimized and the highest occupied molecular orbital energy (EHOMO), the lowest unoccupied molecular orbital energy (ELUMO), energy gap (DE), electronegativity (c), hardness (h), softness (s) and the fraction of electrons transferred from the inhibitor molecule to the metal surface (DN) have been calculated using the DFT/B3LYP and HF methods with the 6-31G(d,p) basis set.